Recent Advances in Carbon Material‐Based Multifunctional Sensors and Their Applications in Electronic Skin Systems. (11th July 2021) - Guo, Yunjian; Wei, Xiao; Gao, Song; Yue, Wenjing; Li, Yang; Shen, Guozhen
Abstract: Electronic skin (e‐skin) is driving significant advances in flexible electronics as it holds great promise in health monitoring, human–machine interfaces, soft robotics, and so on. Flexible sensors that can detect various stimuli or have multiple properties play an indispensable role in e‐skin. Despite tremendous research efforts devoted to flexible sensors with excellent performance regarding a certain sensing mode or property, emerging e‐skin demands multifunctional flexible sensors to be endowed with the skin‐like capability and beyond. Considering outstanding superiorities of electrical conductivity, chemical stability, and ease of functionalization, carbon materials are adopted to implement multifunctional flexible sensors. In this review, the latest advances of carbon‐based multifunctional flexible sensors with regard to the types of detection modes and abundant properties are introduced. The corresponding preparation process, device structure, sensing mechanism, obtained performance, and intriguing applications are highlighted. Furthermore, diverse e‐skin systems by integrating current cutting‐edge technologies (e.g., data acquisition and transmission, neuromorphic technology, and artificial intelligence) with carbon‐based multifunctional flexible sensors are systematically investigated in detail. Finally, the existing problems and future developing directions are also proposed. Abstract : With the coming of the intelligent age, there is an urgent requirement for flexible devices that can achieve omnidirectional imitation of skin functions. This review emphatically summarizes the latest progress of multifunctional flexible sensors and electronic skin systems made of carbon‐based materials as well as their intriguing applications, hoping to promote the development of multifunctional flexible electronics.